Death due to Accidental Explosion of a Balloon Filling Cylinder: A Case Report - Ahamed, Faraz; Ramesh , C; Venkatesha, V T; Ahamed , Ameena (Journal of Indian Academy of Forensic Medicine, 2015)
An explosion is a process where any substance or device capable of creating a sudden gas  expansion, releasing potential energy and thus creating a pressure wave. Blast injury is becoming more  common in non-military population due to terrorist acts and unsafe use of domestic gases, but it is still  rare to see such injuries and deaths. Explosive related deaths fall into three categories: accidental,  homicidal and suicidal. Accidental deaths normally occur either at the work place or when untrained,  unlicensed individuals handle legal or illegal fireworks or explosive/inflammable material. Physicians and  surgeons need to have a basic understanding of the patho-physiology of such injuries, because the major  prognostic factor for favourable outcome is accessible and timely medical and surgical treatment along  with implementations of preventable occupational measures for safety.
Keywords: Cylinder; Traumatic amputation; Explosion; Blast lung; Tympanic membrane rupture